2007
DOI: 10.5210/fm.v12i5.1833
|View full text |Cite
|
Sign up to set email alerts
|

Public libraries, public access computing, FOSS and CI: There are alternatives to private philanthropy

Abstract: In January 2007, The Bill and Melinda Gates Foundation (BMGF) announced its second multi–year technology grant program for America’s public libraries. The purpose of Phase II, Keeping communities connected: The next step is to help public libraries sustain the public access computing infrastructure laid down during Phase I. Now, as then, the goal of the program is to bridge the digital divide. But it is a digital divide as defined by Bill Gates and not the public library community. Situating Gates’ philanthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In 2007, one of the most important institutions combating the digital divide, the Bill and Melinda Gates Foundation (2004), announced a multi‐year technology grant programme for public libraries. This measure was but the latest in a long sequence of similar initiatives; between 1998 and 2004, for example, the Foundation installed 47,200 internet‐linked PCs in 11,000 libraries across the US and trained 62,000 library workers (Stevenson 2007).…”
Section: Public Schools and Librariesmentioning
confidence: 99%
“…In 2007, one of the most important institutions combating the digital divide, the Bill and Melinda Gates Foundation (2004), announced a multi‐year technology grant programme for public libraries. This measure was but the latest in a long sequence of similar initiatives; between 1998 and 2004, for example, the Foundation installed 47,200 internet‐linked PCs in 11,000 libraries across the US and trained 62,000 library workers (Stevenson 2007).…”
Section: Public Schools and Librariesmentioning
confidence: 99%
“…At the same time, Gates' ongoing gifts of software come wrapped in their own proprietary discourse, ready for dissemination among recipient communities. 113 Continuing research into the relationship between public libraries and FOSS -not only as a viable technical and philosophical alternative to proprietary software, but as a modern avatar for labour -might prove enlightening. Second, while the concept of 'useful knowledge' dates back to the earliest days of the republic 114 within an industrial economy, and as reflected in Carnegie's library discourse, only that knowledge of direct (and indirect) utility to capital's circuit of production and circulation was promoted.…”
Section: The Wage Earnermentioning
confidence: 99%
“…Indicatively, Scacchi (2010) concluded that FOSS projects 'are in many ways socio-technical experiments to prototype alternative visions of what innovative systems might be in the near future' on the basis of a mode of governance that effects a 'transformation in the marketplace of ideas and [in] the means of production from centralized authority with corporate enterprises, towards a more decentralized commons-based peer production'. On the same wavelength, Stevenson (2010) called attention to FOSS as an 'organizing vehicle for the world's information workers' and as 'a means to create more open and democratic political systems' (see also Stevenson, 2007), while , in a more recent paper that traces the policy implications of FOSS (and user-generated content, more broadly), underlined the way in which FOSS 'generates value, serves as a medium for cultural expression and allows innovative activity' (see also . Common to all these works is that FOSS is depicted as innovative.…”
Section: Introductionmentioning
confidence: 99%